2019
DOI: 10.1002/adhm.201801158
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Engineering of Functional Nucleic Acid Nanomaterials toward In Vivo Applications

Abstract: equally exciting and perhaps more challenging field of application is toward their in vivo applications, including living animals and human bodies, in diverse areas, [2] such as sensing, drug delivery, medical imaging, and cancer therapy. However, most of these nanomaterials lack selectivity toward targets of interests. Therefore, to employ these nanomaterials for a wider range of in vivo applications, various molecular engineering approaches have been employed to obtained nanomaterials functionalized with bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 235 publications
(283 reference statements)
0
34
0
Order By: Relevance
“…Since DNA oligonucleotides are chemically synthesized, they allow efficient mutation and modication studies. [29][30][31] Recently, it was reported that aer omitting a base on a DNA duplex or Gquadruplex, the scaffold allowed free adenosine or guanosine to re-t into the vacant site. This was achieved either by introducing an abasic-site in the duplex, [32][33][34] or by omitting a whole guanine-nucleotide in a G-quadruplex.…”
Section: Introductionmentioning
confidence: 99%
“…Since DNA oligonucleotides are chemically synthesized, they allow efficient mutation and modication studies. [29][30][31] Recently, it was reported that aer omitting a base on a DNA duplex or Gquadruplex, the scaffold allowed free adenosine or guanosine to re-t into the vacant site. This was achieved either by introducing an abasic-site in the duplex, [32][33][34] or by omitting a whole guanine-nucleotide in a G-quadruplex.…”
Section: Introductionmentioning
confidence: 99%
“…However, the biosensing application of framework nucleic acids based on sizeselective recognition has not been reported. Functional nucleic acids (FNAs) 4,45 , such as aptamers, DNAzymes, and molecular beacons, provide excellent molecular recognition ability, and play important roles in biological analysis [46][47][48][49][50] . Combining the advantage of these two kinds of nucleic acids, we herein develop a DNA molecular sieve for size-selective recognition through the site-specific encapsulation of functional nucleic acids in cavitytunable framework nucleic acids in an efficient and controlled manner.…”
mentioning
confidence: 99%
“…Nucleic acid biopolymers show recognition ability to target molecules with good selectivity. 93 The addition of chemical modifications can impart new chemical properties and biological functions to nucleic acid biopolymers. 94,95 Therefore, the chemically modified nucleic acid biopolymers hold great potential to realize multifunctional biosensing.…”
Section: Application In Biosensingmentioning
confidence: 99%